Is entheses ultrasound reliable? A reading Latin American exercise. Issue 5 (May 2016) - Ventura-Ríos, L.; Navarro-Compan, V; Aliste, M; Linares, M.; Areny, R.; Audisio, M.; Bertoli, A.; Cazenave, T.; Cerón, C.; Díaz, M.; Gutiérrez, M.; Hernández, C.; et al.
Abstract The objective of this study is to evaluate inter-reader entheses ultrasound (US) reliability and the influence of the type of image or degree of sonographer experience on US reliability in patients with spondyloarthritis (SpA). Eighteen Latin American ultrasonographers with different experience took part in an US reading exercise evaluating 60 entheseal images (50 % static images and 50 % videos) from healthy controls and SpA patients. The following sonographic lesions were assessed: structure, thickness, bone proliferation/tendon calcification, erosions, bursitis, and Doppler signal. Another group of three experts with significant experience in entheses US read all images too. Inter-reader reliability among participants and experts was calculated by the Cohen's kappa coefficient. Thresholds for kappa values were <0.2 poor, 0.21–0.4 fair, 0.41–0.6 moderate, 0.61–0.8 good, and 0.81–1 excellent. Furthermore, the results for the expert group were stratified based on the type of image. Kappa correlation coefficients among participants, showed variability depending on the type of lesion, being fair for structure and thickness, moderate for calcifications, erosions, and bursitis, and excellent for Doppler signal. Inter-reader reliability among experts was higher, being moderate for structure and thickness, good for calcifications and bursitis, and excellent for erosions and Doppler. Inter-reader reliability for assessing calcification and structure using static images was significantly higher than for videos. Overall inter-reader reliability for assessing entheses by US in SpA is moderate to excellent for most of the lesions. However, special training seems fundamental to achieve better inter-reader reliability. Moreover, the type of image influenced these results, where evaluation of entheses by videos was more difficult than by static images.